A review of the natural history of adult Cetoniinae (Coleoptera: Scarabaeidae) from Argentina and adjacent countries - Iorio, Osvaldo Di (Zootaxa, 2014)
A compilation of the known natural history of adult Cetoniinae (Coleoptera: Scarabaeidae) from Argentina and adjacent countries is provided. Food items of adult Cetoniinae include pollen and/or nectar (flower visitors), sap and/or slime flux, ripened fruits on plants, green tissues and leaves, and honey. Of the 36 species of Cetoniinae from Argentina, food items are known only for 11 species (30.5%). Attraction to light and bait-traps, adult activity periods, vertebrate predators, and the occurrence in bird nests are presented and discussed. Other insects that share the same food sources and bait-traps with Cetoniinae are mentioned.